Political elite and peacebuilding mechanisms in post-conflict societies (قضايا سياسية, 2025)
This article was prepared by Professor Dr. Walid Salem Mohammed, an Iraqi researcher and professor of political science at the University of Mosul / College of Political Science. He is considered one of the prominent figures in the field of academic studies and his most prominent research contributions include: Institutionalization of Authority and State Building: A Case Study of Iraq, The Problem of the Relationship between the Individual in Arab Government Systems and its Impact on Political Pluralism, Political Opposition in Official Arab Political Analysis, Coexistence of Cultures and Identity Formation: An Introduction to Building the Modern Iraqi State, Mechanisms for Building the Social State in Iraq, The Iraqi Political Elite and the Problems of Function and Role, and other specialized research in the Iraqi and Arab fields that are a reference for researchers and students alike.